Administrative Disposition and Managerial Competency in Dumaguete City’s Lending Institutions - Benedico, Jomar; Ybañez, Romario (Journal of Interdisciplinary Perspectives, 2024)
This study examines the administrative disposition and competency levels of lending institution managers in Dumaguete City, employing a descriptive-correlational research design. A sample of 36 managers was selected as respondents, with data analysis conducted using percentage and weighted mean statistical tools. Findings indicated that the respondents demonstrated very high overall work performance, critical thinking, and professional ethics. Additionally, their appreciation of diversity was rated very high in professionalism and high in administrative disposition. Collaborative competence was also very high in both administrative and professional domains. Lifelong learning was rated high for both administrative disposition and professionalism. Overall, the managers were deemed competent. In terms of job performance, the managers scored high in service provision, very high in work processes, and very high in work relations. A significant relationship was identified between administrative disposition and competence level, particularly concerning collaboration. However, the correlation between competence level and job performance was found to be non-significant for service to others, but significant for both work processes and work relations. The study recommends that managers participate in additional seminars and training to further improve their administrative disposition and competency.